The Marion Experiment : long-term solitary confinement and the supermax movement - Richards, Stephen C. (Elmer H. Johnson and Carol Holmes Johnson series in criminology., 2015)
"The Marion Experiment combines academic research with personal accounts by prisoners to investigate solitary confinement and supermax prisons. USP Marion became a model for supermax prisons, with many other prison systems--in the U.S. and abroad--copying the special architectural and program innovations there"--